Sequential treatment of nitrate and phosphate in groundwater using a permeable reactive barrier system. (15th December 2021) - Buyanjargal, Altantsetseg; Kang, Jiyoung; Sleep, Brent E.; Jeen, Sung-Wook
Abstract: When not properly treated, nitrate and phosphate present in groundwater can damage human health and environments. In this study, laboratory column experiments were performed for sequential treatment of nitrate and phosphate in groundwater. Two columns were set up and connected: one to treat nitrate with organic carbon materials (i.e., woodchips) and the other to treat phosphate with basic oxygen furnace (BOF) slag. The columns were operated for a total of 1.6 years. The results showed that nitrate was removed through denitrification and phosphate was removed by precipitation of the phosphate minerals (e.g., hydroxyapatite). BOF slag was effective at removing phosphate, though the high pH (11–12) of the system's effluent water raised a concern for the downgradient areas. Of the three subsequent experiments performed, pH was near neutral when the effluent of the BOF slag column was passed through local soil. Sparging with CO2 and air, in contrast, resulted in pH levels that were either too low (5 in the case of CO2 ) or too high (9.5 in the case of air). The study shows that sequential permeable reactive barrier (PRB) systems consisting of woodchips and BOF slag can be effective for removal of nitrate and phosphate in groundwater and they can be a long-term remedial solution for groundwater contaminated with both nitrate and phosphate. Highlights: Nitrate and phosphate in groundwater are sequentially treated. Nitrate is removed by denitrification in a woodchip layer. Phosphate is removed by precipitation in a basic oxygen furnace slag layer. High pH from basic oxygen furnace slag can be controlled by passage through soil.